Early management of adult traumatic spinal cord injury in patients with polytrauma: a consensus and clinical recommendations jointly developed by the World Society of Emergency Surgery (WSES) & the European Association of Neurosurgical Societies (EANS) - Picetti, Edoardo (BioMed Central Ltd, 2025)
Background: The early management of polytrauma patients with traumatic spinal cord injury (tSCI) is a major challenge. Sparse data is available to provide optimal care in this scenario and worldwide variability in clinical practice has been documented in recent studies.
Methods: A multidisciplinary consensus panel of physicians selected for their established clinical and scientific expertise in the acute management of tSCI polytrauma patients with different specializations was established. The World Society of Emergency Surgery (WSES) and the European Association of Neurosurgical Societies (EANS) endorsed the consensus, and a modified Delphi approach was adopted.
Results: A total of 17 statements were proposed and discussed. A consensus was reached generating 17 recommendations (16 strong and 1 weak).
Conclusions: This consensus provides practical recommendations to support a clinician's decision making in the management of tSCI polytrauma patients.